Perception on virtual education in university students of Health Sciences, in times of COVID-19 - Callasaca-Goyzueta, Jackelin (2022)
Objective: To know the perception of university students of health sciences about virtual education. Material and methods: Descriptive study in 293 students of the Faculty of Health Sciences of the Jorge Basadre Grohmann National University in Tacna, Peru, during the second semester of the year 2020. A virtual questionnaire with prior informed consent with 26 closed questions was applied. Descriptive statistics were used and data were analyzed with STATA version 16. Results: In the development of virtual classes, students use more cell frequency (65 %) and laptops (62.4 %), with wireless internet (59.3 %). 87.7 % felt that their teaching and training has been affected and is insufficient, due to the lack of adaptation of the teacher to this modality and the lack of audiovisual resources for clinical practice (73.4 %); consider it very important that the practical classes are face-to face (91.1 %). There were negative effects on the socio-economic situation of students (54.6 %) and uncertainty about their academic future. Students perceived problems in their mental health mainly stress (30.3 %) and anxiety (21.5 %); even physical discomfort such as back pain (21.8 %) and burning eyes (21.6 %). Conclusion: The perception of university students of Health Sciences versus virtual education around different learning conditions is negative. They suggest a return to face-to-face classes mainly for clinical practice.